KORELASI KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR PAI SISWA SDN CIHEULEUT 1 KOTA BOGOR - Tatang Muhajang (Universitas Islam Depok, 2023)
This research was carried out using a quantitative correlation research approach to fourth grade students at the Ciheuleut 1 State Elementary School, Bogor City. The purpose of this study was to determine the relationship between emotional intelligence and learning achievement in Islamic Religious Education subjects at Ciheuleut 2 Public Elementary School Bogor City for the 2019/2020 Academic Year. survey method was used to collect data and correlational studies to obtain information about the relationship between emotional intelligence and learning achievement in Islamic religious education. The results of the significance test of the correlation coefficient obtained tcount = 20.56 while ttable with = 0.05 and dk 14 of 2.11. The comparison of the two values ​​shows that tcount > ttable. This means that the correlation between emotional intelligence (X) and learning achievement (Y) is very significant. Because the correlation coefficient obtained is positive, it can be said that the correlation coefficient between emotional intelligence (X) and learning achievement (Y) is positive and very significant. That is, the higher the understanding of emotional intelligence, the higher the learning achievement.